REKONSTRUKSI KONSEP KEPERAWANAN DALAM PERSPEKTIF HUKUM ISLAM: ANALISIS QAWA‘ID FIQHIYYAH DAN QAWA‘ID USHULIYYAH - Nor Aziizah Rahmah; Nursalam Ihsan Insan Budiman; Sardimi (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
This study explores the main question of how Islamic law views the practice of hymen reconstruction, particularly through the lens of Qaw??id Fiqhiyyah and Qaw??id U??liyyah. The issue arises from the social perception that equates virginity with purity, along with the advancement of medical procedures that enable hymen restoration. The study positions itself as a contemporary ijtih?d effort to address modern bioethical concerns within the framework of Islamic jurisprudence. Using a qualitative library research method, this study analyzes classical and contemporary Islamic legal sources through textual interpretation. The findings reveal a divergence of opinion among contemporary scholars regarding the permissibility of such procedures. However, by applying legal maxims such as al-?ar?rah tub?? al-ma???r?t (necessity permits the prohibited) and sadd al-dhar??i? (blocking the means to harm), and considering the objectives of Islamic law (maq??id al-shar??ah), the ruling depends on context, intention, and consequences. This research contributes to the contemporary discourse on Islamic legal perspectives concerning medical intervention and societal concepts of purity.